On the relationship between the fundamental right to life and assisted death (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This paper tackles one of the classic queries surrounding the analysis of the right to life: what is the relationship, if any, between the fundamental right to life and the capacity to end one's own life, especially with the help of others? To answer this question the study explores the meaning of the fundamental right to life paying special attention, on the one hand, to the language used to proclaim it and, on the other, the doctrines of the ECtHR, the Spanish Constitutional Court, the Colombian Constitutional Court, the Supreme Court of Canada, the Italian Constitutional Court and the German Constitutional Court.
Keywords: Right to life; assisted death; right to die; ECHR; ECtHR